Pengaruh Social Media Marketing, Influencer Endorsement, dan Diskon Harga Terhadap Impulsive Buying dengan Trust Sebagai Mediasi pada Produk Parfume Bohe di Kota Denpasar - I Nyoman Augie Widyadhana; Kadek Wulandari Laksmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of social media marketing, influencer endorsements, and price discounts on impulsive purchases with trust as a mediating variable in Bohe Bali perfume consumers. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to Bohe Bali consumers and analyzed using the Partial Least Square (PLS) method. The results showed that social media marketing did not have a significant direct effect on impulsive purchases, but had a positive and significant effect on trust. Conversely, influencer endorsements and price discounts were proven to have a positive and significant direct effect on impulsive purchases. Price discounts were the variable with the strongest direct effect in encouraging impulsive purchases. Furthermore, influencer endorsements and price discounts did not have a significant effect on trust. The test results also showed that trust had a positive and significant effect on impulsive purchases. In testing the mediation effect, trust was proven to fully mediate the influence of social media marketing on impulsive purchases. However, trust was unable to mediate the influence of influencer endorsements and price discounts on impulsive purchases. These findings indicate that social media marketing works through building trust, while influencer endorsements and price discounts encourage impulse purchases through emotional mechanisms and price urgency. The conclusion of this study shows that trust is a key factor in bridging digital marketing strategies with impulse buying behavior, especially for perfume products that are experience goods. Therefore, Bohe Bali needs to balance short-term promotional strategies with efforts to build consumer trust sustainably.